2019
DOI: 10.1186/s13018-019-1198-6
|View full text |Cite
|
Sign up to set email alerts
|

In vivo dynamic motion characteristics of the lower lumbar spine: L4–5 lumbar degenerative disc diseases undergoing unilateral or bilateral pedicle screw fixation combined with TLIF

Abstract: Objective To evaluate the short-term in vivo dynamic motion characteristics of the lower lumbar spine (L3–S1) after unilateral pedicle screw fixation (UPSF) or bilateral pedicle screw fixation (BPSF) combined with TLIF for treatment of L4–5 lumbar degenerative disc diseases (DDD). Methods Twenty-eight patients were recruited (13 UPSF, 15 BPSF). Each patient was CT-scanned to construct 3D models of the L3–S1 vertebrae. The dual fluoroscopic imaging system (DFIS) was then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Spinal stability was analyzed by measuring the range of motion (ROM) and compressive stiffness around the neutral zone of the spinal segment ( Chen et al, 1990 ; Christine et al, 2019 ). Common instrument-related complications were also assessed, including the risk of endplate fracture, degeneration of facet joints, and screw loosening and breakage ( DieeN et al, 1999 ; Nie et al, 2019 ; Xi et al, 2021 ). These risks were assessed using the stress distribution and displacement of the model (Chen et al, 2001 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spinal stability was analyzed by measuring the range of motion (ROM) and compressive stiffness around the neutral zone of the spinal segment ( Chen et al, 1990 ; Christine et al, 2019 ). Common instrument-related complications were also assessed, including the risk of endplate fracture, degeneration of facet joints, and screw loosening and breakage ( DieeN et al, 1999 ; Nie et al, 2019 ; Xi et al, 2021 ). These risks were assessed using the stress distribution and displacement of the model (Chen et al, 2001 ).…”
Section: Methodsmentioning
confidence: 99%
“…Assessing the stability of the lumbar spine, such as ROM and axial stiffness ( Christine et al, 2019 ), is the most important indicator of the effectiveness of surgery. Postoperative complications are a major cause of re-operation and reduced patient quality of life, with endplate fracture, facet joint degeneration, screw loosening, and breakage being the most commonly reported ( DieeN et al, 1999 ; Chang et al, 2017 ; Nie et al, 2019 ; Xi et al, 2021 ). The biomechanical evaluation of screw fixation systems by experimental methods is time-consuming, labor-intensive, and expensive.…”
Section: Introductionmentioning
confidence: 99%
“…This study showed that the increase in axial rotation observed in biomechanics studies does translate to the clinical scenario, with an average left-right twist ROM of 2.11 ± 0.52 degrees for unilateral constructs compared to 0.73 ± 0.32 degrees for bilateral constructs. The authors also reported a reduced effect on adjacent segments with unilateral constructs, as indicated by a reduction in adjacent segment motion [ 5 ]. Unfortunately, no outcome data was included in this report making it difficult to determine the clinical implications of these differences in motion characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous clinical studies have been published in the last decade comparing the efficacy of unilateral and bilateral PLIF and TLIF constructs, underscoring the importance of a sound biomechanical understanding of each treatment modality [5,9,[18][19][20][21]. Results of these studies are not as clear as those biomechanics studies previously discussed in terms of establishing the superiority of unilateral or bilateral pedicle screw fixation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation